2023
DOI: 10.1002/ca.24024
|View full text |Cite
|
Sign up to set email alerts
|

Full‐endoscopic technique for posterior fossa decompression in Chiari malformation type I: An anatomical feasibility study in human cadavers

Abstract: Although endoscope-assisted techniques have been described, a full-endoscopic approach is yet to be performed for posterior fossa decompression (PFD) in Chiari malformation type I (CM-I). This study aims to describe the full-endoscopic PFD technique and evaluate its feasibility. Five fresh-frozen anonymized adult human cadavers were operated on using an endoscope with an oval shaft cross-section with a diameter of 9.3 mm, a working length of 177 mm, and a viewing angle of 20 . It also had an eccentric working … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The purpose of minimally invasive surgery, in all fields, is to decrease this discomfort and provide faster recovery and return to work. 1,2,5 Full-endoscopic procedures are already widely used for spinal procedures, such as disk herniations and spinal stenoses. [6][7][8][9] In the literature, some authors have described minimally invasive and endoscopic techniques for PFD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of minimally invasive surgery, in all fields, is to decrease this discomfort and provide faster recovery and return to work. 1,2,5 Full-endoscopic procedures are already widely used for spinal procedures, such as disk herniations and spinal stenoses. [6][7][8][9] In the literature, some authors have described minimally invasive and endoscopic techniques for PFD.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we demonstrated the feasibility of the full-endoscopic technique for PFD in human cadavers. 5 Here, we present the first cases of PFD in patients with CM performed through a full-endoscopic approach.…”
mentioning
confidence: 99%
“…[18][19][20] The case we have described shows that surgery for CM-I can be performed as a fully endoscopic microsurgical procedure. Based on the clinical anatomical study by Dolas et al, 14 a similar operation was performed.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 One of the aims of minimally invasive techniques is to reduce surgical trauma to the cervical muscles, which directly impacts the rate and speed of postoperative patient recovery. Fully endoscopic surgery for posterior fossa decompression has thus far been described only in cadavers, 14 but the possibilities of endoscopic systems and instruments push the boundaries. We report the case of successful fully endoscopic posterior fossa decompression in a 30-year-old female patient with CM-I.…”
mentioning
confidence: 99%